STRATEGIC CROSSROADS: GEOPOLITICAL DIMENSIONS OF EU–UZBEKISTAN RELATIONS (1991–2024) - Nusratulloyev Shaxzod Amonjon oʻgʻli (TADQIQOTLAR, 2025)
Abstract: This article provides a professional and data-driven analysis of political relations between the European Union (EU) and Uzbekistan from 1991 to 2024. Drawing on a broad range of scholarly literature and official sources, it traces the evolution of EU-Uzbekistan cooperation through stages of diplomatic engagement, sanctions, strategic recalibration, and institutional partnership. Special focus is given to legal frameworks, geopolitical realignments, mutual interests, and recent diplomatic developments. It concludes by outlining the potential trajectory of the relationship amid Uzbekistan’s ongoing reforms and the EU’s evolving priorities in Central Asia.